Volunteer Motivation and Satisfaction in Global Sporting Events: A Comparative Study in the Indian Context - Chakraborti, Rajdeep; Singh, Sweta (Indian Journal of Marketing, 2014)
Sports volunteers play a critical role in the success and smooth running of major sporting events. The purpose of the present study is to study the motivational factors and experiences of the volunteers of the 2010 Commonwealth Games and the 2011 ICC Cricket World Cup held in India. The sample consisted of 153 volunteers from the 2010 Commonwealth Games and 161 volunteers from the 2011 ICC Cricket World Cup. To identify the motivational issues behind volunteerism, SVEMS scale was used and principal component analysis resulted in a four-factor solution. Volunteer satisfaction was measured using a 5-point Likert scale which consisted of three aspects of volunteer satisfaction as proposed by Farrell, Johnston,&Twynam (1998). This study showed that the satisfaction and motivation of volunteers were different for two different mega sporting events (single sporting event vs. multiple sporting event) . The type of event for which volunteers are recruited plays an important role in deciding which factor will lead to a higher level of motivation and satisfaction for the volunteers. The organizing committee can place more emphasis on the satisfaction of the volunteers to enhance the overall experience of volunteerism to ensure that a bunch of committed volunteers are available for the next mega sporting event. Though studies in the European countries have identified the motivating factors behind volunteerism, as per our knowledge, no such study has been conducted in the Indian context to identify the motivating factors for Indian (sports) volunteers. The results of this study show that even in the Indian context, volunteer motivation and satisfaction do not depend on only one factor; rather, it is a combination of different factors which decides whether the volunteers will be satisfied from the facilities provided at such an event and whether they will be motivated to volunteer for such events in the future.